Factors Associated with Difficulty in Returning to School in Students After Traumatic Brain Injury - CHONO, Masayuki; WATANABE, Tomomi; MOMOSAKI, Ryo; TERUYAMA, Junko; NAKAMURA, Mikako; FUKUMOTO, Miki (Journal of UOEH, 2018)
Traumatic brain injury (TBI) often causes behavioral problems and difficulties with school work, but the specific factors associated with difficulty in returning to school after TBI still remain unclear. The purpose of this study was to investigate factors associated with difficulty in returning to school within 1 year of injury in students with traumatic brain injury. This study is a secondary analysis of existing data sets. We recruited patients aged 16 years in the United States with a primary rehabilitation diagnosis of TBI registered in the Traumatic Brain Injury Model Systems National Database. We compared variables between the students who returned to school and those who did not return to school. In addition, subgroup analyses were performed focused on traumatic brain injury severity. We excluded those were received <10 years of schooling, and 309 eligible students were identified for the analysis. Of these, 246 (80%) did not return to school within 1 year of injury. There were fewer cases of severe TBI in the group of students who returned to school than in the group who did not return to school (29% vs 44%, P = 0.03). The duration of rehabilitation was significantly longer in the group who returned to school than in the group who did not return to school (mean days 40 vs 29, P = 0.001), and a subgroup analysis showed in the severe traumatic brain injury group (mean days 46 vs 29; P = 0.02) and the non-severe traumatic brain injury group (mean days 37 vs 26; P = 0.02) similar results. Insufficient amount of rehabilitation was associated with difficulty in returning to school in students after TBI, regardless of the severity of the injury.